Investigation on rapid prototyping of functional porosity gradient parts - Lim, Poh Ling. (2009)
The objectives of this project are to design and fabricate scaffolds with porosity gradient and to analyze the mechanical properties of porosity graded scaffolds compared to uniformly porous scaffolds. Selective Laser Sintering (SLS) is used to build the scaffold using Polycaprolactone (PCL). PCL is is a biodegradable and biocompatible polymer with a slow degradation rate adequate for bone tissue engineering. It comes in the form of powder with an average molecular weight of 50,000, an average size below 100 microns and a density of 1.153 g/cm3. The PCL used in this project is from Solvay Caprolactone. Mechanical properties of bone are being taken into consideration as the scaffold’s study is targeting to bone tissue implant. The structure and the mechanical properties of bones will affect the implant interface